Monetary Awards for Family Violence - Maur, Mary-Jo (Understanding family violence in family court proceedings: providing effective responses for victims, children, and perpetrators, 2025)
"Understanding Family Violence in Family Court Proceedings addresses the growing recognition in Canadian legislation and case law of the need to more effectively address intimate partner violence in family court, with a focus on protecting the safety, well-being, and economic interests of victims and their children post-separation, while also including essential material for professionals working with those who commit family violence. Written by a team of interdisciplinary experts, the book explores various forms of abuse and coercive control, ongoing harassment and emotional abuse after separation, the use of litigation as a tool of abuse, and family violence issues related to parenting and economic matters in post-separation family court cases. Contributors include leading practitioners, scholars in family law and domestic violence, and retired judges, with a foreword by former Chief Justice of Canada, Beverly McLachlin. Offering invaluable insights and practical guidance, Understanding Family Violence in Family Court Proceedings is essential reading for experienced family lawyers, judges, and other professionals, while also providing foundational knowledge for students entering the family justice field or working with survivors of family violence. The book also offers critical perspectives that will make it a valuable addition to gender or feminist studies courses."– Provided by publisher.